Handbook of Biosensors and Biochips 2007
DOI: 10.1002/9780470061565.hbb065
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Biosensor and Microbiosensor Techniques

Abstract: This chapter describes principles and features of thermal biosensors and microbiosensors and includes a discussion of different thermal transducers. A number of instrumental concepts are described in detail from larger flow injection instruments to miniaturized devices and chip designs with thermal arrays. A thermal–electrochemical hybrid sensor is also presented. The chapter contains many descriptions of actual assays from different fields, such as process and in vivo monitoring, multianalyte determination, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The FIA biosensor used in this study has been described elsewhere previously [25]. A schematic of the device setup is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The FIA biosensor used in this study has been described elsewhere previously [25]. A schematic of the device setup is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The single‐channel Enzyme Thermistor device used in this study has been previously described . The setup consists of a peristaltic pump (Gilson Minipuls 2, Villiers‐le‐Bel, France) mounted with one tube for each channel, a pneumatic injection valve with a 100‐μL sample loop (Valco Instrument Co. Inc., Houston, TX, USA) and the Enzyme Thermistor instrument (Omik Bioscience AB, Lund, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Our group has developed a flow‐injected thermal enzyme biosensor, the Enzyme Thermistor. This device detects the heat generated by enzymatic reactions to quantify the presence of specific analytes . To achieve real‐time monitoring, it was necessary to eliminate sample treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has focused on developing biosensors that employ thermal transduction to directly detect the thermal signal generated during enzyme catalysis. The instrument, the enzyme thermistor (ET), has been used to develop a wide range of assays (Xie and Danielsson, 2007). Recently we have shown that the device is capable of quantifying antibiotics in whole blood without any sample pretreatment (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%